Customs Exemptions Law with its Executive Statutes = قانون الإعفاءات الجمركية ولائحته التنفيذية - Egypt. Presidency (2025)
1. Decree of the President of the Arab Republic of Egypt by Law No. 186/1986 promulgating Law on Organizing customs Exemptions -- 2. Decree No. 193/1986 issuing the Executive Statutes for presidential Decree No. 186/1986 promulgating Customs Exemptions.